Special material for biodegradable mulching film, mulching film and preparation method of mulching film
By using biodegradable materials such as PBAT, PLA and PBS, combined with raw materials such as black masterbatch and talc, the problem of high cost and mismatch of functional period of the entire biodegradable mulch is solved, and the performance and cost reduction of mulch is optimized.
Patent Information
- Application Number
- CN202411792843.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-08
- Publication Date
- 2025-03-07
AI Technical Summary
The existing full biodegradable mulch film has high cost, its functional period does not match the crop growth cycle, and it is difficult to achieve material performance optimization.
Biodegradable materials such as PBAT, PLA and PBS are used to optimize the degradation rate and physical properties of the plastic film by reasonably proportioning and adding low-cost raw materials such as black masterbatch and talc.
It effectively reduces the production cost of mulch film, extends the functional period, matches it with the crop growth cycle, and improves the anti-hydrolysis, anti-aging and tensile properties of mulch film.
Smart Images

Figure CN119570212A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fully biodegradable agricultural films, and more specifically relates to a special material for biodegradable mulch film, the mulch film and a preparation method thereof. Background Art
[0002] In response to the environmental problems and economic challenges in the current use of agricultural mulch films, biodegradable mulch films have emerged as an innovative solution to replace traditional non-degradable mulch films, reduce soil pollution and promote green agricultural development. However, in the process of promoting this environmentally friendly technology, there are still several key technical problems that need to be solved.
[0003] First, high cost has become the primary obstacle to the popularization of biodegradable mulch. Specifically, the market price of fully biodegradable mulch is significantly higher than that of ordinary mulch. This price difference makes farmers tend to continue to use traditional mulch for economic reasons, thus hindering the market acceptance and widespread application of biodegradable mulch. Therefore, how to effectively reduce costs through material innovation or production process optimization while ensuring the performance of the mulch has become a technical problem that needs to be solved urgently.
[0004] Secondly, the matching of the functional period of biodegradable mulch with the crop growth cycle cannot be ignored. Existing fully biodegradable mulch has the phenomenon of premature degradation, that is, it begins to decompose before the crops are mature. This not only fails to give full play to the protective effect of the mulch on crops, but may also lead to crop yield reduction and affect farmers' income. How to adjust the degradation rate of the mulch to match it with the growth cycle of specific crops and ensure that the mulch maintains effective protection throughout the crop growth process is the key to improving the application effect of biodegradable mulch.
[0005] In addition, optimizing the performance of the biodegradable mulch material itself is also a major challenge. Take PBAT as an example. Although this material combines flexibility and rigidity, its mechanical strength is relatively low and its degradation cycle is not easy to control. In order to enhance the performance of PBAT and reduce costs, researchers have tried to optimize its comprehensive performance by adding PLA, talc and other additives (such as antioxidants, anti-hydrolysis agents and anti-ultraviolet agents). However, how to accurately control the proportion of these additives without increasing costs to achieve the goal of controlling degradation time and improving mechanical strength while maintaining a low water permeability is a technical difficulty that needs to be overcome in the current research and development of biodegradable mulch. Summary of the invention
[0006] To this end, the present invention provides a special material for biodegradable mulch, mulch and a preparation method thereof, in order to solve the problems of cost, functional period matching and material performance optimization of biodegradable mulch in the prior art, so as to achieve the purpose of reducing the cost of biodegradable mulch and improving its anti-hydrolysis, anti-aging and anti-tensile properties, as well as meeting the requirements of the crop growth cycle during the functional period.
[0007] To achieve the above-mentioned purpose, in a first aspect, the present invention provides a special material for preparing a fully biodegradable mulch film, wherein the special material comprises the following raw materials in parts by weight: 70 to 90 parts of PBAT; 1 to 10 parts of PLA; 1 to 10 parts of PBS; 4 to 5 parts of black masterbatch; 1 to 20 parts of talc; 0.1 to 5 parts of lubricant; 0.1 to 2 parts of anti-hydrolysis agent; 0 to 5 parts of plasticizer; 0.1 to 1.5 parts of coating agent; 0.1 to 1.5 parts of antioxidant; 0.1 to 1.5 parts of anti-ultraviolet agent; 0.1 to 1 parts of compatibilizer; and 0.1 to 1 parts of nucleating agent.
[0008] The special material for preparing the fully biodegradable mulch provided by the present invention adopts biodegradable materials such as polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA) and polybutylene succinate (or polybutylene succinate, PBS). Among them, the relatively cheap PBAT is selected as the main component, and the cost is effectively controlled through reasonable proportioning. In order to further reduce the cost, low-cost raw materials such as black masterbatch and talcum powder are also added to the special material. The addition of black masterbatch makes the mulch appear black, which not only enhances the heat absorption capacity of the mulch, is conducive to heating and heat preservation, but also effectively inhibits the growth of weeds and reduces the cost of weed control. The addition of talcum powder helps to improve the physical properties of the mulch. In addition, an appropriate amount of lubricants, anti-hydrolysis agents and other additives are added to the special material to improve the chemical stability of the mulch, such as water retention, tensile strength and elongation at break. The addition of these additives makes the mulch have better durability and tear resistance during use, and effectively prevents degradation or aging caused by environmental factors such as light and moisture. It is worth noting that biodegradable materials such as PBAT, PLA and PBS in special materials have different degradation rates. By precisely adjusting the ratio of these materials, the degradation rate of the mulch can be controlled to match the growth cycle of the crop. In the early stage of crop growth, the mulch maintains its integrity to provide heat preservation and moisture retention; in the later stage of growth, the mulch gradually degrades to reduce soil pollution. In addition, compatibilizers are added to special materials to improve the compatibility between different raw materials, making the mulch easier to plasticize and shape during the preparation process and improving the overall performance. At the same time, the addition of nucleating agents improves the crystallization properties of the mulch, improves transparency and gloss, and impact resistance.
[0009] In some preferred embodiments of the present invention, the method for preparing the special material comprises the following steps: Thermal drying and dehydration: thermal drying the PBAT, PLA, PBS and black masterbatch to a moisture content of less than 0.5%, the thermal drying temperature is 50-80° C., and the thermal drying time is about 0-5 hours; Material mixing: pre-heat-treat the talcum powder at 105° C. for 0 to 3 h, and then cool it to room temperature until the moisture content is below 0.5%. All raw materials are put into a high-speed mixer according to the proportion. Specifically, they can be mixed at 500 to 1000 r / min for 50 to 120 s, and then at 1000 to 2000 r / min for 0 to 60 s, and mixed evenly to obtain a mixed material; Extrusion granulation: the mixed material is put into a twin-screw extruder, and the extrusion temperature is set at 140° C. to 170° C. to obtain the special material.
[0010] The above preparation method ensures the dryness of the raw materials, lays a solid foundation for the subsequent material mixing and extrusion granulation, and helps to improve the quality stability of the final product. Secondly, the material mixing stage adopts a mixing strategy of first low speed and then high speed, which not only ensures the full and uniform mixing of the raw materials, but also avoids the degradation of the materials caused by excessive shearing, and retains the best performance of the raw materials. The present invention uses a twin-screw extruder to perform extrusion granulation within a suitable temperature range, which further improves its processing performance and physical properties.
[0011] According to some embodiments of the present invention, the PBAT melt index is 3 to 5 g / 10 min, and the terminal carboxyl group is less than 10. The melt index (melt index) refers to the mass of molten plastic passing through a standard orifice per unit time at a certain temperature and pressure, reflecting its flow properties in a molten state. This indicator is highly sensitive to the flow properties, processing properties and thermal stability of PBAT, and is usually between 2 and 15 g / 10 min. Through a large number of experiments, it was found that the molecular weight, molecular structure and processing conditions of PBAT with a melt index of 3 to 5 g / 10 min are more suitable for preparing the special material for the fully biodegradable mulch film of the present invention. Selecting such a PBAT raw material can ensure the stability and controllability of the material during the processing while ensuring good fluidity, which is conducive to improving the molding effect and dimensional accuracy of the final product. PBAT with a low terminal carboxyl content has good shear resistance, which helps to reduce the degradation and aging of the material during processing and use, delay film breakage, and extend the functional period, thereby extending the service life of the product and maintaining the excellent performance of the product. If the terminal carboxyl content of PBAT is too high, it is easy to promote the breakage of the ester bond, shortening the functional period.
[0012] According to some embodiments of the present invention, the melting point of the PLA is 150-170°C. If a PLA with a melting point that is too high is selected, the processing temperature of the special material and the ground film also needs to be increased accordingly, which firstly increases energy consumption and equipment loss, and secondly is not conducive to the thermal degradation of the degradable material. The preferred melting point is 150-170°C, which shows a wider adaptability in processing and application, while maintaining good thermal stability and mechanical properties, and also reduces costs to a certain extent.
[0013] According to some embodiments of the present invention, the PBS in the special material has a melting point of ≥110°C, a melt index of 3-8g / 10min, and a terminal carboxyl group of <20. Excessive melt index and terminal carboxyl groups can easily lead to the breakage of the ground film product, which is not conducive to processing and use. The PBS that meets the above conditions ensures good processing fluidity of the material, can ensure stability and durability in high temperature environments, and broadens its application range, especially in occasions that need to withstand higher temperatures, and has a relatively extended functional period.
[0014] In some embodiments of the present invention, the talc powder has a particle size of less than 5 μm and a fineness of ≥ 5000 mesh. The talc powder meeting such requirements has good dispersibility and is evenly distributed in the special material, exerting better water-blocking performance.
[0015] In some preferred embodiments of the present invention, the antioxidant is obtained by mixing one or more of antioxidant 168, antioxidant 1076, antioxidant 1010, and antioxidant 246 with phosphites and organic sulfide antioxidants. By mixing one or more of antioxidant 1076, antioxidant 1010, and antioxidant 246 with phosphites and organic sulfide antioxidants, a more comprehensive and efficient antioxidant system can be formed. This combination can not only capture and neutralize free radicals to prevent thermal oxidative degradation of materials during processing and use, but also significantly improve the antioxidant properties of materials and extend the service life of products through the synergistic effect of different action mechanisms.
[0016] Preferably, the lubricant is obtained by mixing one or more of liquid paraffin, stearic acid monoglyceride, and polyethylene wax in any ratio. The selection and ratio design of the above lubricants make the material have better fluidity and demoulding properties during processing, reduce energy consumption and wear during processing, and improve production efficiency. At the same time, the mixed use of liquid paraffin, stearic acid monoglyceride, polyethylene wax and other ingredients can adjust the lubrication performance according to specific processing requirements to achieve more refined processing control.
[0017] Preferably, the black masterbatch is obtained by mixing and extruding carbon black and PBAT in a weight ratio of 1:2. The black masterbatch is obtained by mixing and extruding carbon black and PBAT (polyethylene terephthalate / butylene adipate copolymer) in a weight ratio of 1:2, which not only ensures that the black mulch film can keep warm and increase soil moisture and inhibit weeds in the early stage, but also makes full use of the biodegradability of PBAT and slowly degrades accordingly, making it possible to produce environmentally friendly and high-performance black plastic products.
[0018] Preferably, the anti-ultraviolet agent is obtained by mixing one or more of light stabilizer T68, light stabilizer 944, light stabilizer 622, light stabilizer 119, light stabilizer T69, and light stabilizer 2020 in any ratio. By mixing multiple light stabilizers (such as T68, 944, 622, 119, T69, 2020, etc.), a wide-spectrum anti-ultraviolet system can be formed to effectively resist the destructive effect of ultraviolet rays on materials, protect the color, gloss and physical properties of materials, and extend the life of outdoor products.
[0019] Preferably, the anti-hydrolysis agent is obtained by mixing one or more of polymeric carbodiimide, monomeric carbodiimide, and TGIC in any proportion. The mixed use of polymeric carbodiimide, monomeric carbodiimide, TGIC and other anti-hydrolysis agents can significantly improve the stability of the material in an aqueous environment, prevent performance degradation and failure due to hydrolysis, and broaden the application range of the material, especially in a humid or underwater environment.
[0020] Preferably, the compatibilizer is one or more of BASF 4400, 4468, BP96, and KL4370 mixed in any proportion. The above compatibilizers are specially designed to improve the compatibility between different polymers. They can significantly reduce the interfacial tension between different components, promote uniform dispersion and close bonding between components, thereby improving the overall performance and stability of the composite material, and help improve the mechanical properties of the composite material such as tensile strength, impact strength and toughness, making the material more durable and reliable. At the same time, it can also improve the processing fluidity of the material, reduce energy consumption and wear during processing, and improve production efficiency.
[0021] Preferably, the nucleating agent is a mixture of one or more organic nucleating agents selected from carboxylic acid metal salts, phosphate metal salts, and sorbitol benzyl derivatives in any proportion. Organic nucleating agents such as carboxylic acid metal salts, phosphate metal salts, and sorbitol benzyl derivatives can promote the orderly arrangement and crystallization process of polymer molecules, thereby increasing the crystallization rate and crystallinity of the material, and helping to improve the mechanical properties and heat resistance of the material. It can refine the grain size of the polymer, improve uniformity and density, help improve the transparency and glossiness of the material, reduce the brittleness of the material, and improve toughness, thereby reducing the internal stress and shrinkage during processing, and improving the dimensional stability and surface quality of the product.
[0022] The second aspect of the present invention provides a biodegradable mulch film, at least one layer of which is prepared using the special material described in the first aspect of the present invention. Of course, in actual production, depending on the structure of different biodegradable mulch films, such as multi-layer biodegradable mulch films, each layer can be prepared using the special material described in the first aspect of the present invention, or one or more layers can be prepared using the special material described in the first aspect of the present invention.
[0023] In some preferred embodiments, the preparation method of the biodegradable mulch film comprises putting the special material into a film blowing machine for preparation, wherein the screw temperature is 140°C to 190°C, the tee temperature is 150°C to 190°C, the die processing temperature is 160 to 190°C, and the film thickness is 8μm to 12μm. The above process conditions can ensure that the physical properties of the biodegradable mulch film, such as tensile strength, tear strength, and impact strength, are optimized, so that it has better durability and reliability during use. The degradation rate and degradation products of the biodegradable mulch film can be regulated to minimize the negative impact on the environment while meeting the needs of agricultural production.
[0024] In some preferred embodiments, the functional period of the biodegradable mulch provided by the present invention is 70 to 90 days, the water vapor permeability coefficient is less than 5, the elongation at break is 300 to 500% after artificial ultraviolet aging for 120 hours, and the tensile strength is 25 to 27 MPa. Compared with traditional mulch, the biodegradable mulch of the present invention has a longer service life, can better meet the needs of the agricultural production cycle, and does not need to be frequently replaced during use, thereby reducing labor intensity and production costs. The water vapor permeability coefficient is less than 5, indicating that the biodegradable mulch of the present invention has excellent moisture retention performance, can effectively curb the loss of soil moisture, maintain soil moisture, provide a good growth environment for crops, and contribute to the root development and nutrient absorption of crops, thereby improving the yield and quality of crops. After 120 hours of artificial ultraviolet aging, the elongation at break is 300 to 500%, indicating that the biodegradable mulch of the present invention can still maintain high flexibility and elongation at break after long-term exposure to ultraviolet rays, is not easy to age, and can better resist the erosion of environmental factors (such as ultraviolet rays, wind, rain, etc.) during outdoor use, thereby extending the service life and functional period. The tensile strength is 25-27 MPa, which shows that the biodegradable mulch film of the present invention has high mechanical strength, can withstand certain external forces and pressures, ensures integrity and stability during laying and use, and is not easily damaged or deformed.
[0025] Different from the prior art, the above technical solution adopts a variety of biodegradable materials such as PBAT, PLA and PBS, and uses the cheaper PBAT as the main component, but the cost can be controlled to a certain extent through reasonable proportioning. At the same time, by adding an appropriate amount of low-cost raw materials such as black masterbatch, talcum powder, and using an appropriate amount of lubricants, anti-hydrolysis agents and other additives, the cost can be further reduced while ensuring the performance of the mulch. The biodegradable materials such as PBAT, PLA and PBS in the special material of the present invention have different degradation rates. By adjusting the ratio of these materials, the degradation rate of the mulch can be controlled so that it matches the growth cycle of the crop. In the early stage of crop growth, the black masterbatch makes the mulch appear black, which is more easy to absorb heat, which is conducive to heating and heat preservation. The mulch can maintain good integrity and provide heat preservation and moisture retention effects; in the later stage of crop growth, the mulch needs to be gradually degraded to reduce soil pollution. Black mulch can also effectively inhibit the growth of weeds and reduce weed control costs. By adding talcum powder, lubricants, antioxidants, anti-hydrolysis agents, anti-ultraviolet agents and other raw materials, the physical properties of the ground film are effectively improved, and the chemical stability of the ground film is improved, such as improving the water retention, tensile strength, elongation at break, etc. of the ground film, strengthening PBAT and reducing production costs, and meeting the requirements of agricultural machinery film laying and sowing, and not deforming or breaking when stretched, so that it has better durability and tear resistance during use, and effectively prevents the ground film from being degraded or aged due to environmental factors such as light and moisture during use. The added compatibilizer can improve the compatibility between different raw materials, making the ground film easier to plasticize and shape during the preparation process, while improving the overall performance of the ground film. By adding a nucleating agent, the crystallization performance of the ground film can be improved, so that the ground film has better transparency and gloss during use, and the impact resistance of the ground film is improved.
[0026] The above-mentioned records related to the invention content are only an overview of the technical solution of the present application. In order to enable ordinary technicians in the field to more clearly understand the technical solution of the present application, and then implement it according to the text of the specification and the contents recorded in the drawings, and to make the above-mentioned purpose and other purposes, features and advantages of the present application easier to understand, the following is an explanation in combination with the specific implementation mode and drawings of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only used to illustrate the principles, implementation methods, applications, characteristics and effects of the specific embodiments of the present application and other related contents, and shall not be considered as limitations of the present application.
[0028] In the drawings of the specification: Figure 1 It is a schematic diagram of the extrusion molding process of the special material described in the specific implementation method; Figure 2The figure is a schematic diagram of the film blowing process flow of the biodegradable mulch film according to the specific implementation method. DETAILED DESCRIPTION
[0029] In order to explain in detail the possible application scenarios, technical principles, specific schemes that can be implemented, and the purposes and effects that can be achieved, the following is a detailed description of the specific embodiments listed in conjunction with the accompanying drawings. The embodiments described herein are only used to more clearly illustrate the technical solutions of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0030] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.
[0031] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.
[0032] In the description of this application, the term "and / or" is an expression used to describe the logical relationship between objects, indicating that three relationships may exist, for example, A and / or B, which means: A exists, B exists, and A and B exist at the same time. In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" logical relationship.
[0033] In the present application, terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship of quantity, priority or sequence between these entities or operations.
[0034] Without further limitations, in this application, the words "include", "comprises", "has" or other similar expressions used in the sentences are intended to cover non-exclusive inclusion. These expressions do not exclude the presence of additional elements in the process, method or product including the elements, so that the process, method or product including a series of elements may include not only those limited elements, but also other elements not explicitly listed, or also include elements inherent to such process, method or product.
[0035] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than", "less than", "exceed" and the like are understood to exclude the number itself; expressions such as "above", "below", "within" and the like are understood to include the number itself. In addition, in the description of the embodiments of this application, "multiple" means more than two (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups", "multiple times", etc., unless otherwise clearly and specifically limited.
[0036] In the description of the embodiments of the present application, space-related expressions used, such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "vertical", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicate the orientation or position relationship based on the orientation or position relationship shown in the specific embodiments or drawings, and are only for the convenience of describing the specific embodiments of the present application or facilitating the reader's understanding, and do not indicate or imply that the referred device or component must have a specific position, a specific orientation, or be constructed or operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.
[0037] Unless otherwise expressly specified or limited, in the description of the embodiments of the present application, the terms such as "install", "connect", "connect", "fix", "set", etc. used should be understood in a broad sense. For example, the "connection" can be a fixed connection, a detachable connection, or an integrated setting; it can be a mechanical connection, an electrical connection, or a communication connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For technicians in the technical field to which the present application belongs, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0038] In the present invention, the raw materials PBAT and PBS used are from Xinjiang Blue Mountain Tunhe Technology Co., Ltd., and PLA is from Anhui Fengyuan Group Co., Ltd., Zhejiang Hisun Biomaterials Co., Ltd., Total SA, France, etc. Unless otherwise specified, other raw materials and auxiliary reagents are conventional commercial products in the field. Example
[0039] See also Figure 1 and Figure 2 This embodiment discloses a method for preparing a fully biodegradable mulch film, and the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0040] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0041] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0042] (4) Material mixing: by weight, add 80 parts of PBAT, 5 parts of PLA, 5 parts of PBS, 10 parts of talc, 0.4 parts of coating agent, 0.4 parts of stearic acid monoglyceride, 0.8 parts of polyethylene wax, 0.4 parts of antioxidant 168, 0.4 parts of antioxidant 1010, 0.8 parts of TGIC, 0.2 parts of carbodiimide, 0.6 parts of anti-ultraviolet agent or light stabilizer 622, 0.15 parts of compatibilizer, and 0.15 parts of nucleating agent into a high-speed mixer according to the proportions. Set the speed to 750r / min for 60s and 1500r / min for 20s to mix evenly.
[0043] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0044] (6) Blown film: Add 4-5 parts of carbon black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0045] This embodiment discloses a method for preparing a fully biodegradable mulch film, and the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0046] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0047] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0048] (4) Material mixing: by weight, add 78 parts of PBAT, 5 parts of PLA, 7 parts of PBS, 10 parts of talc, 0.4 parts of coating agent, 0.4 parts of stearic acid monoglyceride, 0.8 parts of polyethylene wax, 0.5 parts of antioxidant 168, 0.3 parts of antioxidant 1010, 1.0 parts of TGIC, 0.3 parts of anti-ultraviolet agent (light stabilizer) 622, 0.3 parts of anti-ultraviolet agent T68, 0.2 parts of compatibilizer, and 0.2 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0049] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0050] (6) Blown film: Add 4-5 parts of carbon black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0051] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0052] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0053] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and masterbatch at 50°C for 3 hours.
[0054] (4) Material mixing: by weight, add 80 parts of PBAT, 5 parts of PLA, 5 parts of PBS, 10 parts of talc, 0.4 parts of coating agent, 0.4 parts of stearic acid monoglyceride, 0.8 parts of polyethylene wax, 0.2 parts of antioxidant 168, 0.3 parts of antioxidant 1076, 1.0 parts of TGIC, 0.3 parts of anti-ultraviolet agent (light stabilizer) 622, 0.3 parts of anti-ultraviolet agent 119, 0.3 parts of compatibilizer, 0.3 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0055] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0056] (6) Blown film: Add 4-5 parts of carbon black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0057] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0058] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0059] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0060] (4) Material mixing: by weight, add 82 parts of PBAT, 5 parts of PLA, 3 parts of PBS, 10 parts of talc, 0.4 parts of stearic acid monoglyceride, 0.8 parts of polyethylene wax, 0.4 parts of antioxidant 168, 0.4 parts of antioxidant 1010, 0.8 parts of TGIC, 0.2 parts of carbodiimide, 0.8 parts of anti-ultraviolet agent (light stabilizer) 622, 0.3 parts of compatibilizer, and 0.5 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0061] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0062] (6) Blown film: Add 4-5 parts of carbon black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0063] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0064] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0065] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0066] (4) Material mixing: by weight, add 80 parts of PBAT, 3 parts of PLA, 2 parts of PBS, 15 parts of talc, 0.4 parts of stearic acid monoglyceride, 0.8 parts of polyethylene wax, 0.4 parts of antioxidant 168, 0.4 parts of antioxidant 1010, 0.8 parts of TGIC, 0.2 parts of carbodiimide, 0.8 parts of anti-ultraviolet agent (light stabilizer) 622, 0.5 parts of compatibilizer, and 0.5 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0067] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0068] (6) Blown film: Add 4-5 parts of black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0069] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0070] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0071] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0072] (4) Material mixing: by weight, add 82 parts of PBAT, 5 parts of PLA, 3 parts of PBS, 10 parts of talc, 0.6 parts of coating agent, 0.5 parts of stearic acid monoglyceride, 1 part of polyethylene wax, 0.2 parts of antioxidant 168, 0.4 parts of antioxidant 1076, 0.5 parts of TGIC, 0.1 parts of carbodiimide, 0.3 parts of anti-ultraviolet agent (light stabilizer) 622, 0.3 parts of anti-ultraviolet agent T68, 0.1 parts of compatibilizer, and 0.1 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0073] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0074] (6) Blown film: Add 4-5 parts of black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8~12μm. Example
[0075] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0076] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0077] (3) Thermal dehydration: Thermally bake PBAT, PLA, PBS, and black masterbatch at 50°C for 3 hours.
[0078] (4) Material mixing: by weight, add 80 parts of PBAT, 3 parts of PLA, 2 parts of PBS, 15 parts of talc, 0.8 parts of coating agent, 0.5 parts of stearic acid monoglyceride, 1 part of polyethylene wax, 0.2 parts of antioxidant 168, 0.3 parts of antioxidant 1076, 0.3 parts of type carbodiimide, 0.3 parts of anti-ultraviolet agent 622, 0.3 parts of anti-ultraviolet agent 119, 0.1 parts of compatibilizer, and 0.1 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0079] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0080] (6) Blown film: Add 4-5 parts of black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8-12μm.
[0081] A method for preparing a fully biodegradable mulch film, the preparation method is as follows: (1) Heat treatment of talcum powder: Heat the talcum powder at 105℃ for 3 hours, then cool it to 50℃ and keep it at a constant temperature for 2 hours.
[0082] (2) Preparation of black masterbatch: The black masterbatch is extruded and granulated according to the ratio of carbon black and PBAT of 1:2.
[0083] (3) Thermal dehydration: Thermally bake PBAT, PPC, and black masterbatch at 50°C for 3 hours.
[0084] (4) Material mixing: by weight, add 70 parts of PBAT, 20 parts of PPC, 10 parts of talc, 0.8 parts of coating agent, 0.5 parts of stearic acid monoglyceride, 1 part of polyethylene wax, 0.2 parts of antioxidant 168, 0.4 parts of antioxidant 1010, 0.8 parts of TGIC, 0.2 parts of carbodiimide, 0.8 parts of anti-ultraviolet agent (light stabilizer) 622, 0.3 parts of compatibilizer, and 0.3 parts of nucleating agent into a high-speed mixer according to the proportions. Mix at 750 r / min for 60 seconds and 1500 r / min for 20 seconds until evenly mixed.
[0085] (5) Extrusion granulation: The mixed material is fed into a twin-screw extruder at an extrusion temperature of 130°C to 180°C to obtain a fully biodegradable mulch film material.
[0086] (6) Blown film: Add 4-5 parts of black masterbatch to the special material for fully biodegradable mulch film and mix evenly. Then put it into the feed port of the film blowing machine. The screw temperature is 145℃~175℃, the die processing temperature is 165~185℃, and the film thickness is 8-12μm.
[0087] The test method for the relevant properties of the biodegradable mulch film in the present invention is as follows: Tensile strength: Tested according to GB / T 13022 "Test method for tensile properties of plastic films".
[0088] Initial elongation at break: Tested in accordance with GB / T 13022 “Test method for tensile properties of plastic films”.
[0089] Elongation at break after 120h artificial UV aging: tested in accordance with GB / T 16422.3-2022 "Plastics laboratory light source exposure test method Part 3: Fluorescent UV lamp".
[0090] MFR change rate after boiling for 120 hours: put the modified special material into a covered glass bottle filled with pure water at a boiling temperature of 70°C, take samples every 24 hours, test their MFR after drying, and calculate the MFR change rate of the modified special material.
[0091] Water vapor permeability coefficient: tested in accordance with GB / T1037-2021 "Plastic film and sheeting water vapor permeability performance determination cup weight gain and weight loss method".
[0092] The functional period refers to the time period from the laying of the ground film to its gradual degradation and loss of its main functions such as insulation and moisture retention. In the present invention, it refers to the period from mid-to-late April to mid-to-late August each year when the film is laid.
[0093] The biodegradable mulch films obtained in Examples 1-7 and Comparative Example 1 were subjected to performance tests according to the above method. The results are shown in Table 1.
[0094] Table 1 Performance test results of biodegradable mulch films (materials) obtained in Examples 1-7 and Comparative Example 1 Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Comparative Example 1 Tensile strength(MPa) 26.0 25.8 26.5 26.2 27.0 24.8 17.0 16.5 Initial elongation at break (%) 463 475 460 558 489 423 420 392 Elongation at break after 120h artificial UV aging (%) 332 312 327 434 428 260 233 / MFR change rate after boiling for 120 hours (%) 53.1 84.1 73.9 46.2 39.1 135.9 120.6 / <![CDATA[Water vapor transmission coefficient g*cm(cm 2 *s*Pa)]]> 8.9 8.5 7.2 4.6 3.2 10.2 10.8 12.9 Function period (days) ≥80 ≥75 ≥70 ≥90 ≥85 ≥60 ≥50 / From the results in Table 1, it can be seen that the biodegradable mulch films of Examples 1-7 have optimized suitable raw materials and their proportions (such as antioxidants, anti-ultraviolet agents and anti-hydrolysis agents), which ensures the effective functional period of the fully biodegradable mulch films and matches them with the growth cycle of crops.
[0095] From the experimental data of Examples 4-5 and 6-7, it can be seen that when the amount of talc added is 10-15 parts and the amount of compatibilizer and nucleator added is 0.3-0.5 parts, thanks to the advantages of talc such as excellent dispersibility and water barrier properties and low cost, the compatibilizer improves the compatibility between different raw materials to make the mulch easier to plasticize and form, and the nucleator improves the crystallization performance and impact resistance of the mulch, which improves the physical properties of the mulch as a whole. In addition, an appropriate amount of lubricant, anti-hydrolysis agent and other additives are added to the special material to improve the chemical stability of the mulch, such as water retention, tensile strength and elongation at break, so that the mechanical properties, UV resistance and hydrolysis resistance, water barrier properties and functional period of the prepared fully biodegradable mulch are optimal. When the amount of chain extender and nucleator is reduced to 0.1 parts (Example 7), the performance of the mulch deteriorates.
[0096] It can be seen from the experimental data of Examples 1-3 and Example 6 that when the dosage of the anti-hydrolysis agent is 1 part, the change rate of the MFR of the fully biodegradable mulch modified material is smaller, and its anti-hydrolysis ability is enhanced.
[0097] From the experimental data of Example 5, it can be seen that by adding 0.5 parts of compatibilizer and nucleating agent and 0.8 parts of anti-ultraviolet agent, the water vapor permeability coefficient of the fully biodegradable mulch film is below 4, the functional period can reach more than 90 days, and the other properties are better.
[0098] From the experimental data of Examples 1-7 and Comparative Example 1, it can be seen that after completely replacing PLA and PBS with 20% PPC, the performance (tensile strength, initial elongation at break and water vapor permeability coefficient) is not as good as that of Examples 1-7, and the higher price of PPC increases the cost of the fully biodegradable mulch film.
[0099] Finally, it should be noted that although the above embodiments have been described in the specification and drawings of this application, this does not limit the scope of patent protection of this application. All technical solutions generated by replacing or modifying equivalent structures or equivalent processes based on the essential concept of this application using the contents recorded in the specification and drawings of this application, as well as directly or indirectly implementing the technical solutions of the above embodiments in other related technical fields, are included in the scope of patent protection of this application.
Claims
1. A special material for preparing a fully biodegradable mulch film, characterized in that: The special material contains the following raw materials by weight: PBAT 70-90 parts; PLA 1-10 parts; PBS 1-10 parts; Black masterbatch 4-5 parts; 1-20 parts of talcum powder; Lubricant 0.1-5 parts; 0.1-2 parts of anti-hydrolysis agent; Plasticizer 0-5 parts; 0.1 to 1.5 parts of coating agent; 0.1-1.5 parts of antioxidant; 0.1-1.5 parts of anti-ultraviolet agent; Compatibilizer 0.1-1 part; Nucleating agent 0.1 to 1 part.
2. The special material according to claim 1, characterized in that: The preparation method of the special material comprises the following steps: Thermal drying and dehydration: thermal drying the PBAT, PLA, PBS and black masterbatch to a moisture content of less than 0.5%; Material mixing: pre-heat-treating the talcum powder, and uniformly mixing all the raw materials according to a proportion to obtain a mixed material; Extrusion granulation: the mixed material is put into a twin-screw extruder, and the extrusion temperature is set at 140° C. to 170° C. to obtain the special material.
3. The special material according to claim 1, characterized in that: The PBAT has a melt index of 3 to 5 g / 10 min and a terminal carboxyl group of less than 10.
4. The special material according to claim 1, characterized in that: The melting point of the PLA is 150-170°C.
5. The special material according to claim 1, characterized in that: The PBS has a melting point of ≥110° C., a melting index of 3-8 g / 10 min. and terminal carboxyl groups of <20.
6. The special material according to claim 1, characterized in that: The talcum powder has a particle size of less than 5 μm and a fineness of ≥5000 mesh.
7. The special material according to claim 1, characterized in that: The antioxidant is obtained by mixing one or more of antioxidant 168, antioxidant 1076, antioxidant 1010, and antioxidant 246 with phosphites and organic sulfide antioxidants; Preferably, the lubricant is obtained by mixing one or more of liquid paraffin, stearic acid monoglyceride, and polyethylene wax in any ratio; Preferably, the black masterbatch is obtained by mixing carbon black and PBAT in a weight ratio of 1:2 and extruding; Preferably, the anti-ultraviolet agent is obtained by mixing one or more of light stabilizer T68, light stabilizer 944, light stabilizer 622, light stabilizer 119, light stabilizer T69, and light stabilizer 2020 in any proportion; Preferably, the anti-hydrolysis agent is obtained by mixing one or more of polymeric carbodiimide, monomeric carbodiimide, and TGIC in any proportion; Preferably, the compatibilizer is one or more of BASF 4400, 4468, BP96, and KL4370 mixed in any proportion; Preferably, the nucleating agent is a mixture of one or more organic nucleating agents selected from carboxylic acid metal salts, phosphate metal salts, and sorbitol benzyl derivatives in any proportion.
8. A biodegradable mulch film, characterized in that: At least one layer is prepared using the special material described in any one of claims 1 to 7.
9. The biodegradable mulch film according to claim 8, characterized in that: The preparation method of the biodegradable mulch film comprises the steps of feeding the special material into a film blowing machine, wherein the screw temperature is 140°C to 190°C, the tee temperature is 150°C to 190°C, the die processing temperature is 160°C to 190°C, and the film blowing thickness is 8μm to 12μm.
10. The biodegradable mulch film according to claim 8, characterized in that: The functional period is 70 to 90 days, the water vapor permeability coefficient is less than 5, the elongation at break is 300 to 500% after 120 hours of artificial UV aging, and the tensile strength is 25 to 27 MPa.
Citation Information
Cited By
Method for prolonging service life of biodegradable mulching film material
CN120850798A